Orientation on Individualistic versus Collectivistic Values as the Basis for Explaining Pupils? Cooperation - Bąbka, Jarosław (INSTED: Interdisciplinary Studies in Education & Society, 2012)
Changes in the contemporary world are manifested by shifting from society-oriented attitude to a more individualistic approach, from responsibility to self-accomplishment, from cooperation to freedom and competition. In view of the changes towards individualism, the problem of cooperation among junior high school students entering adulthood, so far neglected in educational studies, has been approached. The article searches for prerequisites of the relation between individualism versus collectivism and the readiness of an individual to cooperate. Individualism is related to the self-orientation, whereas collectivism means ?towards others? attitude. Theoretical analyses are completed with the analysis of a section of research on treating adolescents’ orientation on individualistic versus collectivistic values as a factor differentiating cooperation under task situations. It does not mean, however, that adolescents stopped appreciating collectivistic values. This tendency complies with the decisions made by other authors. The hypothesis about the difference in results concerning cooperative behaviours depending on a particular orientation, namely on individualistic and collectivitis values, has not been confirmed. At this level of the analysis there are no grounds for concluding whether the individualistic or the collectivistic orientation is more in favour of cooperation. It is probable that cooperation involves both individualistic as well as collectivistic values. It is in agreement with the views of other authors that individualism and collectivism can co-exist. The considerations in the paper are a reason for seeking possibilities of joining personal interest of an individual with pro-community cooperation, which is an important issue in terms of conceptualisation of the vision of the community as well as in terms of the undertaken educational activities for young generation.